2016
DOI: 10.1021/acsami.6b04239
|View full text |Cite
|
Sign up to set email alerts
|

Large Polarization of Li4Ti5O12 Lithiated to 0 V at Large Charge/Discharge Rates

Abstract: The ability to enhance the specific capacity of Li4Ti5O12 (LTO) is of practical significance and offers the opportunity to increase the energy density of a full LTO-based battery. Widening the discharge cutoff voltage to 0 V is an effective way to increase the capacity of LTO at low current density. However, whether the specific capacity of LTO at large current rates can be enhanced remains largely unknown. Herein, intriguingly, we found that, when cycled down to 0 V (i.e., from 1.0-2.5 to 0-25 V), LTO exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…[52] Lu et al [141] observed an abnormal interface layer on lithiated Li 4 Ti 5 O 12 samples using spherical aberration-corrected scanning transmission electron microscopy (STEM). Han et al [142] found that, when cycled down to 0 V at low rates (<5 C), Li 4 Ti 5 O 12 exhibited a greatly enhanced specific capacity; meanwhile at high rates (>10 C), the capacity rapidly faded, and the composite demonstrated a greatly increased charge/discharge potential gap. The stable reversible cycling capacity reached ≈330 mA h g −1 .…”
Section: Excess Discharge For More Specific Capacitymentioning
confidence: 99%
“…[52] Lu et al [141] observed an abnormal interface layer on lithiated Li 4 Ti 5 O 12 samples using spherical aberration-corrected scanning transmission electron microscopy (STEM). Han et al [142] found that, when cycled down to 0 V at low rates (<5 C), Li 4 Ti 5 O 12 exhibited a greatly enhanced specific capacity; meanwhile at high rates (>10 C), the capacity rapidly faded, and the composite demonstrated a greatly increased charge/discharge potential gap. The stable reversible cycling capacity reached ≈330 mA h g −1 .…”
Section: Excess Discharge For More Specific Capacitymentioning
confidence: 99%
“…Extra discharge capacity and higher nominal voltage can be achieved with LTO as anode material when using the overlithiated phase. However, previous studies show that optimum utilization of this extra capacity still needs more mechanistic studies and large irreversible capacities have previously been attributed to the large polarization caused by substantial activation energy [55], the stability of the overlithiated phase [23,43] and SEI formation.…”
Section: Lithiated and Overlithiated Structuresmentioning
confidence: 99%
“…Insertion‐type electrodes, include Li 4 Ti 5 O 12 , TiO 2 (anatase, bronze), TiNb 2 O 7 , Nb 2 O 5 , Li 3 VO 4 , H 2 Ti 6 O 13 , LiMnBO 3 , etc., have been explored for LIHC applications . The volume change accompanying this Li intercalation process is comparatively small (nearly 0% for Li 4 Ti 5 O 12 and <4% for anatase TiO 2 ), which ensures the structural integrity of the host lattice and renders high coulombic efficiency and long cycling life …”
Section: Metal Oxidesmentioning
confidence: 99%
“…Lithium titanate (Li 4 Ti 5 O 12 , LTO) is the firstly studied anode material for LIHC due to the following advantages: 1) the spinel structure of LTO provides a three‐dimensional network of channels for lithium ion diffusion, giving excellent rate capability for Li insertion and extraction, in particular at high charging/discharging rate; 2) the crytal structure undergoes almost no volume changes during Li insertion/extraction process, which ensures a long cyclic life and high coulombic efficiency; and 3) safe charging and discharging at a constant potential of 1.55 V versus Li/Li + , which is above the deposition potential of lithium ions and the reduction potential of most electrolytes or solvents . These properties render LTO a promising anode candidate for LIHC.…”
Section: Metal Oxidesmentioning
confidence: 99%